Kemampuan Siswa dalam Membuat Teks Deskripsi Berdasarkan Media Gambar - Munawaroh, Anisa Bahtiar, Prof. Dr. Markhamah, M.Hum (2016)
Abstract This research has two aim. 1. Expose the ability to write a Garland of description on the suitability of the title and the content of the image. 2. Expose the ability to write a Garland of description of aspects of word choice or diction in grade VII Junior High School Muhammadiyah Surakarta 5. The type of research used in this research is descriptive qualitative. The data in this study is the word, the sentence in the text of the description made by the students, who have experienced errors in particular areas of syntax or diction word choice IE. The technique of data collection in this study by using techniques and documentation, refer to the note. Based on the data that has been analyzed, found two types of analysis. 1. Analysis of aspects of the suitability of the description, the title with the contents of the image there is 40%, the text doesn't match the title with image content of 20%. 2. Found seven errors on the syntax field selections that include the word or diction errors capitalization error 22%, 34%, said the choice of sentence not clear 16%, 26% abbreviation usage mistakes, mistakes the use of pronouns (-nya) 6%, error prepositions (di-) 12%, and the use of the word hyphen mistake 6%. The results of this research can be used as a method of teaching in junior high school about students ' ability in making or writes a text description with the use of media images.